2005
DOI: 10.1103/physrevd.71.034505
|View full text |Cite
|
Sign up to set email alerts
|

Monopole content of topological clusters: Have Kraan-van Baal calorons been found?

Abstract: Using smearing of equilibrium lattice fields generated at finite temperature in the confined phase of SU (2) lattice gauge theory, we have investigated the emerging topological objects (clusters of topological charge). Analysing their monopole content according to the Polyakov gauge and the maximally Abelian gauge, we characterize part of them to correspond to nonstatic calorons or static dyons in the context of Kraan-van Baal caloron solutions with non-trivial holonomy. The behaviour of the Polyakov loop insi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…In IMCG, the situation for dyon charge induced vortices is rather stable: we find always a space-time vortex connecting the dyons or better to say the Abelian monopoles representing the dyons in MAG [8,32]. Similar to the LCG doublet case two vortex lines pass near the center of mass of the caloron.…”
Section: E Results From Maximal Center Gaugesmentioning
confidence: 92%
See 1 more Smart Citation
“…In IMCG, the situation for dyon charge induced vortices is rather stable: we find always a space-time vortex connecting the dyons or better to say the Abelian monopoles representing the dyons in MAG [8,32]. Similar to the LCG doublet case two vortex lines pass near the center of mass of the caloron.…”
Section: E Results From Maximal Center Gaugesmentioning
confidence: 92%
“…Far away from the caloron's dyons, however, the ''hedgehog'' È is not ''combed'' completely and there is no need for a singularity. 8 In other words the covering of the color space happens in an exponentially small but finite solid angle.…”
Section: B the Twistmentioning
confidence: 99%
“…Applying naively the simple sum-ansatz (14) would induce an interaction between calorons even at infinite separations. This is the first caloron-specific problem appearing in superpositions.…”
Section: Superposing Calorons: a First Approach And Its Problemsmentioning
confidence: 99%
“…The emphasis is put on gases or liquids of calorons and anticalorons. The main motivation for this development came from lattice studies [12,13,14,15], stimulated by the knowledge of the basic features of the new caloron solutions. These lattice studies aimed at and were successfully identifying structures resembling instantons or calorons in ab-initio Monte Carlo gauge fields, in a similar spirit as earlier instanton (caloron) searches at zero (non-zero) temperature [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Polyakov loop averaged over the low-action region of the lattice was proposed to play the role of the asymptotic holonomy in the infinite continuum. As for generic equilibrium configurations, recent smearing studies revealed clusters of topological charge, that -according to their content of Abelian monopoles and the corresponding behaviour of the Polyakov loop -have charges close to either ±1 or ±1/2, resembling calorons and their constituents, respectively [27].…”
Section: Calorons -In the Continuum And On The Latticementioning
confidence: 99%